Self-assessment of football referees on their educational influence on children aged 9-12 during a sports competition - Płoszaj Katarzyna; Firek Wiesław (Sciendo, 2021)
Proper use of the educational potential of sports depends on the entities organizing children's sports competitions (coaches, parents, referees). Particularly important is their awareness of the purposefulness and legitimacy of actions taken. Numerous studies have been devoted to the role of the coach and parents in providing children and young people with positive sporting experiences. In contrast, the referee has often been overlooked. The behavior of the referees during the match is also important for young players. Assuming that referee-player interactions have a major contribution to educational influence, the purpose of this study was to explore the opinions of soccer referees refereeing matches of children aged 9 to 12 years about their interactions with players in terms of emotional support, game organization, and instructional support. It was also decided to verify whether referees' self-assessment of their educational function is influenced by experience. The research was conducted among 116 referees licensed by Mazovian Football Association who referee matches of children aged 9-12 years (Orliki and Młodziki categories) in the Masovian Voivodeship in Poland. To assess the referee-players educational interaction, a questionnaire survey was developed. These interactions are present in three domains: emotional support, game organization and instructional support. The results showed significant differences between referees' self-assessments in the three domains. Referees rated their educational interactions with players higher in the domain of emotional support than the instructional support. Moreover, the results indicated that there was no differences in the referees' self-assessment between the groups distinguished by more experienced in the domains of emotional support and game organization, while less experienced referees rated the quality of their educational interactions in the instructional support domain higher than those more experienced. The main conclusion of the research is the postulate to introduce pedagogical and psychological issues into the referee training.